2011
DOI: 10.3892/ol.2011.255
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Hodgkin’s lymphoma in clinical practice: A retrospective long-term follow-up analysis

Abstract: Abstract. Treatment of Hodgkin's lymphoma (HL) is perceived to be relatively straightforward. Consequently, patients are not usually referred to hemato-oncologically specialized centres and are treated locally instead. Comprehensive findings beyond prospective controlled trials are therefore lacking. Clinical data of 209 patients who had received a HL diagnosis were collected. A total of 7 patients received radiotherapy (RT) alone (3%), 75 (35%) were treated with a combination of chemotherapy (CT) and RT and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…In our cohort, the percentage of cHL and NLPHL were 88.7% and 11.3%; respectively. NS subtype was more prominent than MC, 55% and 22.5% respectively, which is similar to several European and US studies [16,21]. On the other hand, some developing countries showed that MC subtype was more prominent than NS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our cohort, the percentage of cHL and NLPHL were 88.7% and 11.3%; respectively. NS subtype was more prominent than MC, 55% and 22.5% respectively, which is similar to several European and US studies [16,21]. On the other hand, some developing countries showed that MC subtype was more prominent than NS.…”
Section: Discussionsupporting
confidence: 88%
“…Other countries with low socioeconomic level showed a similar percentage [19], Sherief et al showed a higher percentage of advanced stage 56% in comparison to the early stage 44% [17]. In contrast, the European countries with higher socioeconomic level showed a lower percentage of advanced disease, may be due to early diagnosis, Aquino et al showed early and advanced stages, 70% and 30%, respectively [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our whole cohort revealed a male-to-female ratio of 2.2:1; this male predominance and other patients and disease characteristics at relapse were reported in many other studies (27)(28)(29). The percentage of patients with first treatment failure whether refractory or early and late relapse was also comparable to what was reported in the literature (7) (9).…”
Section: Discussionsupporting
confidence: 88%